Fuzzy model of vehicle delay to determine the level of service of two-lane roads. (15th July 2016) - Martín, Sergio; Romana, Manuel G.; Santos, Matilde
Highlights: A fuzzy model for determining delayed vehicles on two-way two-lane roads based on drivers' perceptions. The level of service is obtained using the estimated vehicle delay state and the overtaking maneuver. An extension of the possible states of a vehicle is defined including overtaking desire. Simulation results have been successfully compared with the behavior of two-lane road drivers. Abstract: The level of service (LOS) on two-lane highways and, therefore, the quality of traffic flow, is currently estimated based on the delay of the vehicles and, in certain types of roads, the average travel speed. Speed is relatively easy to measure. However, it is important, and not so simple, to determine whether a vehicle is delayed. Traditional methods, generally based on quantitative measurements of average time between vehicles and thresholds, fail to take into account the inherent vagueness of the driving process. In this paper, we have developed a fuzzy model that gives a new and reliable method for determining such vehicle state on two-way two-lane roads, based on drivers' perceptions. The proposed system is composed of seven fuzzy subsystems that take into account imprecise knowledge, human factors, and subjective perceptions regarding the road, the car, the driver, environmental conditions, etc. Simulation results of the system have been successfully compared with the behavior of two-lane road drivers who were interviewed. The level of service of these facilities is obtained using the estimated vehicle delay state and the overtaking maneuver. Therefore, this proposal makes it possible to introduce these existing driving experiences into LOS assessment and accordingly, it is potentially a step forward since LOS must be related, by definition, to user experience. These results could be used in future frameworks. In addition, an extension of the possible states of a vehicle is defined. This approach takes into account the drivers point of view regarding overtaking desire and in this sense, it is closer to reality.